The biological effects of individual-level PM2.5 exposure on systemic immunity and inflammatory response in traffic policemen - Zhao, Jinzhuo; Gao, Zhiyi; Tian, Zhenyong; Xie, Yuquan; Xin, Feng; Jiang, Rongfang; Kan, Haidong; Song, Weimin (Occupational and environmental medicine (London, England), 2013)
Background Ambient fine-particle particulate matter (PM2.5) exposure is associated with the decline in pulmonary function, prevalence of coronary heart disease and incidence of myocardial infarction. The study is to observe the effects of ambient PM2.5 on the cardiovascular system and to explore the potential inflammatory and immune mechanisms. Methods The subjects included 110 traffic policemen in Shanghai, China, who were aged 25–55 years. Two-times continuous 24 h individual-level PM2.5 measurements were performed in winter and summer, respectively. The inflammatory marker (high-sensitivity C-reactive protein, hs-CRP), immune parameters (IgA, IgG, IgM and IgE) and lymphocyte profiles (CD4 T cells, CD8 T cells, CD4/CD8 T cells) were measured in blood. The associations between individual-level PM2.5 and inflammatory marker and immune parameters were analysed by multiple linear regression. Results The average concentration of 24 h personal PM2.5 for participants was 116.98 μg/m3 and 86.48 μg/m3 in winter and summer, respectively. In the main analysis, PM2.5 exposure is associated with the increases in hs-CRP of 1.1%, IgG of 6.7%, IgM of 11.2% and IgE of 3.3% in participants, and decreases in IgA of 4.7% and CD8 of 0.7%, whereas we found no statistical association in CD4 T cells and CD4/CD8 T cells. In the adjusted model, the results showed that the increase of PM2.5 was associated with the changes of inflammatory markers and immune markers both in winter and summer. Conclusions Traffic policeman have been a high-risk group suffering inflammatory response or immune injury because of the high exposure to PM2.5. These findings provided new insight into the mechanisms linking ambient PM2.5 and inflammatory and immune response.